The Commonest Negative Behavioral Manifestations among Kindergarten Children in the Post-Terrorist Phase: شيماء حارث محمد , امل داود سليم (Journal of the College of Education for Women, 2021)
Behavioral and emotional disorders represent one of the commonest problems facing children in particular and disturbing their parents and educators in general. This is because Iraqi people have long been living in difficult conditions and faced various terrorists’ operations, such as killing, destruction, robbery, and looting. Such operations are said to be one of the reasons that leads to the development of such disorders, and may negatively affect the psyche of the child and be reflected on his behavior as represented by playing with the IPad for hours, and suffering from nightmares. Accordingly, the current research aims to examine specifically the commonest negative behavioral disorders among kindergarten children during the post-terrorist phase. To achieve this objective, the researchers prepared a tool for measuring the commonest behavioral manifestations among kindergarten children, and distributed it to a sample of (160) children’s female teachers and mothers; each using a multi-stage method. Results have shown that the computed value of (t-test) reached (17.793) for female teachers’ estimations and (6,653) for mother's estimations. That is, the computed value is greater than the tabulated, (1.96), at the level of significance (0.05) and degree of freedom (159.( The highest degree of severity belongs to the behavioral aspect of playing with the iPad for long hours according to the teachers’ estimates. It has scored (3.843) with a weight percentage that is equal to (96.075). However, the same behavioral aspect has a severity degree that is equal to (3.59) with a weight percentage reaches (89.825) from the parent’s perspectives. As for the second manifestation, thinking of the death of a family member, its severity has scored (3.593) with a weight percentage of (89.82) according to the parents’ estimates, whereas the severity degree of the behavioral manifestation, suffering from disturbing dreams and nightmares, is (3.55) with a weight percentage....